Personal Religiosity of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Personal religiosity holds significance as it provides individuals with a framework for understanding existence, moral guidance, and a sense of belonging, contributing to their overall well-being and sense of purpose in life. Specific practices of individuals need to be explored to understand what needs to be improved within the curricular offerings of faith-centered institutions. This study determined the personal religious practices of the respondents in terms of daily routine, religious belief, and school- related scenarios. This study utilized quantitative descriptive-correlation research method, employing adapted questionnaire administered online to 159 Junior High School students at Union Christian College. Weighted mean was used to describe the variables, while Pearson Product Moment Correlation was utilized to determine the relationship between their profile and their personal religiosity. The findings reveal that the religious practices of students related to daily routines, religious beliefs, and school activities are high which shows that they showed positive attitudes towards it. While they are high, they are not considered optimal which means that an intervention has to be done. Positive significant correlation was found between their personal religiosity and their religious affiliation, which infers that their faith is connected to the extent to which they practice personal religiosity. The researchers recommend the use of a Religious Practice Checklist during Edukasyon sa Pagpapahalaga (ESP) and homeroom periods for the Junior High School students to maintain and improve their religious practices, and strengthen their connection with their faith.
Keywords: faith; personal religiosity; religion